2019
DOI: 10.1111/irv.12695
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel influenza A virus exposures by an improved high‐throughput multiplex MAGPIX platform and serum adsorption

Abstract: Background The development of serologic assays that can rapidly assess human exposure to novel influenza viruses remains a public health need. Previously, we developed an 11‐plex magnetic fluorescence microsphere immunoassay (MAGPIX) by using globular head domain recombinant hemagglutinins (rHAs) with serum adsorption using two ectodomain rHAs. Methods We compared sera collected from two cohorts with novel influenza exposures: animal shelter staff during an A(H7N2) outbreak in New York City in 2016‐2017 (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…S1 and S2 in the supplemental material) (16). In our previous studies, we used a serum dilution of 1:40 to detect influenza virus antibody responses using the same assay platform (14,15,17). Here, the linearity analysis suggests that the 1:40 serum dilution falls well within the linear range for most seasonal and novel subtype influenza virus antigens and is suitable to capture the full scope of the antibody responses to most antigens while maintaining the assay throughput.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…S1 and S2 in the supplemental material) (16). In our previous studies, we used a serum dilution of 1:40 to detect influenza virus antibody responses using the same assay platform (14,15,17). Here, the linearity analysis suggests that the 1:40 serum dilution falls well within the linear range for most seasonal and novel subtype influenza virus antigens and is suitable to capture the full scope of the antibody responses to most antigens while maintaining the assay throughput.…”
Section: Resultsmentioning
confidence: 97%
“…To determine seroconversion in the MIADA for paired serum samples, we used a $2-fold rise in MFIs after adjustment of low S1 MFIs to 1,000 (14,15). We found that one A(H1N1)pdm09-infected person and three A(H3N2)-infected persons achieved seroconversion ($2-fold rises in MFIs) against at least one novel subtype rHA (H5, H7, H9, or H13) (Tables S3 and S4), and nine persons showed high MFIs ($2,000) against a novel subtype rHA(s) in S2 and/or S1 sera, although no seroconversions in MFIs were achieved (Table S5 and data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations